Honmeric Candy (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Turmeric, originating from the rhizomes of the turmeric plant, is significant in culinary traditions, particularly Asian cuisines.  This spice has enjoyed a prominent role as curry's primary flavoring agent, infusing them with its distinctly warm and slightly bitter taste.  Beyond its culinary applications, turmeric has been harnessed for various purposes, extending into the realms of medicine and cosmetics.  Notably, curcumin, a vibrant yellow compound residing within turmeric, has found employment as a coloring agent for various foods and cosmetics and as a key factor in its potential health benefits. The turmeric root, rich in curcumin, has been tapped extensively for its therapeutic potential.  Curcumin, renowned for its vivid yellow hue, has played a pivotal role in coloring diverse consumables and cosmetic products.  This natural compound has been embraced for its potential health-promoting properties, serving as the cornerstone for numerous medicinal applications.  One noteworthy aspect of its usage lies in addressing conditions characterized by pain and inflammation, such as the case of osteoarthritis.  This has been complemented by the spice's historical employment in treating ailments like hay fever, depression, high cholesterol, and certain liver disorders.  Furthermore, the root's intrinsic properties mitigate itching and offer relief in various scenarios. While folk wisdom attributed numerous benefits to turmeric, such as aiding heartburn, bolstering cognitive faculties, and combating inflammatory diseases, scientific validation for these claims remained wanting.  Rigorous empirical evidence to substantiate these assertions needed more robust, underscoring the need for well-designed studies to elucidate these potential effects. Conversely, honey, a natural substance derived from the nectar of flowers by bees, boasts its own nutritional attributes.  These golden liquid carries trace amounts of vital B vitamins, including riboflavin, niacin, folic acid, pantothenic acid, and vitamin B6.  Additionally, honey contains ascorbic acid (vitamin C) alongside a medley of essential minerals such as calcium, iron, zinc, potassium, phosphorus, magnesium, selenium, and chromium.  The amalgamation of these nutrients lends honey its reputation as a nutrient-rich superfood. In pursuit of innovative culinary creations, a feasibility study delved into synthesizing a confection that combined the wholesome qualities of honey with the aromatic and beneficial elements of turmeric.  This fusion birthed the concept of "Homeric candy," aiming to cater to candy enthusiasts' palates while offering a potential healthful twist.  The study's outcome revealed a resounding vote of confidence in the Homeric candy, with participants attesting to its excellence across facets such as taste, texture, aroma, and packaging. The study's results pave the way for a recommendation to embark on a comprehensive market analysis.  This step is pivotal to ensure the venture's viability and profitability while upholding the unwavering quality standard of the product.  By marrying the attributes of turmeric and honey in a delightful confection, this innovative venture holds promise as a delectable treat and a harmonious marriage of two nature-endowed powerhouses.
Keywords: honmeric; healthy treat; feasibility study